"Fusion and binding inhibition" key target for HIV-1 treatment and pre-exposure prophylaxis: targets, drug delivery and nanotechnology approaches. (1st January 2017) - Malik, Tanushree; Chauhan, Gaurav; Rath, Goutam; Murthy, R. S. R.; Goyal, Amit K.
Abstract: More than 35 million people are living with HIV worldwide with approximately 2.3 million new infections per year. Cascade of events (cell entry, virus replication, assembly and release of newly formed virions) is involved in the HIV-1 transmission process. Every single step offers a potential therapeutic strategy to halt this progression and HIV fusion into the human host cell is one such stage. Controlling the initial event of HIV-1 transmission is the best way to control its dissemination especially when prophylaxis is concerned. Action is required either on the HIV's or host's cell surface which is logically more rational when compared with other intracellular acting moieties. Aim of this manuscript is to detail the significance and current strategies to halt this initial step, thus blocking the entry of HIV-1 for further infection. Both HIV-1 and the possible host cell's receptors/co-receptors are under focus while specifying the targets available for inhibiting this fusion. Current and under investigation moieties are categorized based on their versatile mechanisms. Advanced drug delivery and nanotechnology approaches present a key tool to exploit the therapeutic potential in a boosted way. Current drug delivery and the impact of nanotechnology in potentiating this strategy are detailed.